Development of a novel, entirely herbal-based mouthwash effective against common oral bacteria and SARS-CoV-2 - Bálint Bencze; Viktória Temesfői; Sourav Das; Henrietta Papp; Péter Kaltenecker; Anett Kuczmog; Ferenc Jakab; Béla Kocsis; Tamás Kőszegi (BMC, 2023)
Abstract Background Parallel to the growth of the oral healthcare market, there is a constantly increasing demand for natural products as well. Many customers prefer products that contain fewer toxic agents, therefore providing an environmentally friendly solution with the benefit of smaller risk to the user. Medieval and early modern medicinal knowledge might be useful when looking for natural, herbal-based components to develop modern products. Along with these considerations we created, tested, and compared an entirely natural mouthwash, named Herba Dei. Methods The manufacturing procedure was standardized, and the created tincture was evaluated by GC/MS analysis for active compounds, experimentally tested in cell-based cytotoxicity, salivary protein integrity, cell-free antioxidant activity, anti-bacterial and anti-viral assays, and compared with three market-leading mouthwashes. Results Our tincture did not show significant damage in the cytotoxicity assays to keratinocyte and Vero E6 cells and did not disrupt the low molecular weight salivary proteins. Its radical scavenging capacity surpassed that of two tested, partly natural, and synthetic mouthwashes, while its antibacterial activity was comparable to the tested products, or higher in the bacterial aerobic respiratory assay. The active compounds responsible for the effects include naturally occurring phenylpropanoids, terpenes, and terpenoids. Our mouthwash proved to be effective in vitro in lowering the copy number of SARS-CoV-2 in circumstances mimicking the salivary environment. Conclusions The developed product might be a useful tool to impede the transmission and spread of SARS-CoV-2 in interpersonal contact and aerosol-generating conditions. Our mouthwash can help reduce the oral bacterial flora and has an antioxidant activity that facilitates wound healing and prevents adverse effects of smoke in the oral cavity.